The influences of Guru Penggerak on the Pancasila students’ profile of elementary schools - Awaludin, Yusuf (Indonesian Journal of Curriculum and Educational Technology Studies, 2023)
Education is essentially not just about developing cognitive abilities, but also about the character of students. The main problem of this research is related to the nation's noble values ​​and morals, which are associated with the character of students who do not match the Pancasila student profile. These character problems occur throughout Indonesia, not only in cities but also in villages. Guru Penggerak plays an essential role in the process of developing the character of students at school. This research aims to determine the influence of Guru Penggerak on the profile of Pancasila students. The research method uses survey research with correlation techniques. The results of the research show that the profile of Pancasila students is influenced by Guru Penggerak, namely as agents of change in the world of education whose role is to create believers who have faith in God Almighty and have noble morals, global diversity, mutual cooperation, independence, critical reasoning and creativity. Guru Penggerak is expected to focus more on guiding students to learn according to their potential and needs but must still be in accordance with the Pancasila student profile. Abstrak Pendidikan pada hakikatnya tidak hanya mengembangkan kemampuan kognitif, tetapi juga karakter siswa. Permasalahan utama penelitian ini adalah terkait dengan nilai-nilai luhur dan moral bangsa yang berkaitan dengan karakter mahasiswa yang tidak sesuai dengan profil mahasiswa Pancasila. Permasalahan karakter ini terjadi di seluruh Indonesia, tidak hanya di kota tetapi juga di desa. Guru penggerak memegang peranan penting dalam proses pengembangan karakter siswa di sekolah. Tujuan dari penelitian ini adalah untuk menjawab pengaruh guru penggerak terhadap profil siswa Pancasila. Metode penelitian menggunakan penelitian survei dengan teknik korelasi. Hasil penelitian menunjukkan bahwa profil siswa Pancasila dipengaruhi oleh guru penggerak, yaitu sebagai agen perubahan dalam dunia pendidikan yang berperan menciptakan manusia yang beriman dan bertaqwa kepada Tuhan Yang Maha Esa dan berakhlak mulia, berwawasan kebangsaan, gotong royong, mandiri, bernalar kritis dan kreatif. Guru penggerak diharapkan lebih fokus dalam mengarahkan siswa untuk belajar sesuai dengan potensi dan kebutuhannya namun harus tetap sesuai dengan profil siswa Pancasila.